Nativization of Dissertation Acknowledgements and Private Letters in Cameroon - Daniel A. Nkemleke (Nordic Journal of African Studies, 2006)
One very important area of research on English in the “Outer Circle” has been on the extent to which text types have become nativized in the home culture. Yet, there seems to be a dearth of interest in this domain of study in Cameroon. With ample evidence from dissertation acknowledgements and private letters, this study assesses the cultural-specific indicators that make these text types distinctive. Because these texts are culturally and situationally highly bound, the investigation relies not only on the Sociolinguistic Approach generally used in such analyses, but also on the Cultural-based Approach and Grice’s Co-operation Principle. Two hundred dissertation acknowledgements and 222 private letters have been used. And findings reveal that both text types show a greater degree of adaptation to the “culture of community” characteristic of traditional African lifestyle. For example, the general configuration of dissertation acknowledgements, and to a certain extent private letters, reflect the “good manners” of deference to elders and those who have played an important role in the writer’s life and success. Other contextually determined features such as the transfer of native devices for personalizing speech interaction are frequent. The study concludes that while text-type research remains a rich area of study in view of the establishment of a profile of Cameroon-specific features of new Englishes, it is equally a good basis on which to investigate the ethnography of culture. Here linguistics and cultural studies will find a useful match.